Risk factors for subsequent vertebral fractures after percutaneous vertebral augmentation in Asian populations: a systematic review and meta-analysis - Weijie Zheng; Jiexin Huang; Liang Jin; Qiaoli Zhang; TianFeng Li; WanChen Gong; Yuchen Xia; Zhengyi Lin; Fei Zhou; Chengwu Lu; Libao Zhang; Changhui Xue; et al. (BMC Musculoskeletal Disorders)
Abstract Objective To identify the risk factors for subsequent vertebral fractures after percutaneous vertebral augmentation through the meta-analysis. Methods Articles from 2019 to 2024 were retrieved from PubMed, Cochrane Library, Embase, and Web of Science. The quality of included studies was assessed using the Newcastle–Ottawa Scale (NOS), while data analysis was performed with R (The R Project for Statistical Computing). Results Fourteen articles comprising data from 5,673 patients were included in the analysis. Statistically significant differences were identified for age, gender, T-score (measured by dual-energy X-ray absorptiometry), body mass index (BMI), Computed tomography Hounsfield unit (CT HU) value, intravertebral cleft (IVC), multi-segment vertebral fractures, and bone cement leakage. In contrast, no statistically significant differences were observed for hypertension history, diabetes history, thoracolumbar vertebral fracture, postoperative Cobb angle, surgical method（percutaneous vertebroplasty/percutaneous kyphoplasty）, puncture method (unilateral/bilateral puncture), or bone cement volume. Conclusion In Asian populations, advanced age, female, low T-score, low BMI, low CT HU values, presence of IVC, multi-segment vertebral fractures, and bone cement leakage are identified as significant risk factors for subsequent vertebral fractures following PVA. Conversely, a history of anti-osteoporosis treatment is identified as a protective factor, whereas hypertension history, diabetes history, thoracolumbar vertebral fracture, postoperative Cobb angle, surgical method, puncture method, and bone cement volume demonstrate no significant correlation with subsequent vertebral fractures after PVA.